2020
DOI: 10.3390/ijms21124370
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and ROS Crosstalk in Cardiac and Pulmonary Diseases

Abstract: Reactive oxygen species (ROS) affect many cellular functions and the proper redox balance between ROS and antioxidants contributes substantially to the physiological welfare of the cell. During pathological conditions, an altered redox equilibrium leads to increased production of ROS that in turn may cause oxidative damage. MicroRNAs (miRNAs) regulate gene expression at the post-transcriptional level contributing to all major cellular processes, including oxidative stress and cell death. Several miRNAs are exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 239 publications
(298 reference statements)
1
66
0
Order By: Relevance
“…It was reported that production of reactive oxygen species (ROS) upregulated miR-206 expression (57,58). Interestingly, IL-13, a type 2 cytokine, promotes ROS production in airway epithelial cells (59).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that production of reactive oxygen species (ROS) upregulated miR-206 expression (57,58). Interestingly, IL-13, a type 2 cytokine, promotes ROS production in airway epithelial cells (59).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main risk factors of BPD in premature infants is hyperoxia exposure, which signi cantly increase the risk of pneumonia and retinopathy of prematurity (ROP). It has been previously shown that hyperoxia induced lung injury (or oxygen toxicity) is mainly mediated by reactive oxygen species (ROS), while ROS production is related to infection, in ammatory reaction and mitochondrial respiration [27,28]. Choo-Wing et al [29] found that the combined treatment of hyperoxia exposure and interferon gamma on neonatal mice caused ERS to occur in lung tissues, as well as upregulated the expression of cyclooxygenase-2 (Cox2) and apoptosis of epithelial cells at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…In endothelial cells, miR-199a expression has been shown to promote cell survival, proliferation, migration, and tube formation [ 126 ]. miR-199a expression plays a protective role in the cardiomyocytes of MI, and downregulation of miR-199a expression is observed in the presence of ROS [ 127 ]. Meanwhile, other recent studies suggest the opposite opinion and deny the cardioprotective function demonstrated by miR-199a.…”
Section: Cvd-related Mirnas Target Enos and Sirt1mentioning
confidence: 99%